2007
DOI: 10.1093/esr/jcm013
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Formal and Informal Social Capital in Europe

Abstract: Studies of social capital have concentrated upon either formal associative behaviour or informal social relations (networks). This article looks at the relationship between these two ty'pes of social capital by examining social networks, social and family support (informal social capital) on the one hand and associational behaviour along with social trust (formal social capital) on the other. Using the Eurobarometer 62.2 covering a representative sample of 27 countries the analysis found that with this approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
198
1
21

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(231 citation statements)
references
References 31 publications
11
198
1
21
Order By: Relevance
“…For the nation states, the differences obtained confirm well-known results from other studies, according to which-local-civil-society engagement in post-socialist countries (here in the Polish and Czech border regions) is comparatively low [69]. Differences to the German and French border regions were sizable: One-way ANOVAs with subsequent Scheffé tests were significant at p < 0.01.…”
Section: Resultssupporting
confidence: 87%
“…For the nation states, the differences obtained confirm well-known results from other studies, according to which-local-civil-society engagement in post-socialist countries (here in the Polish and Czech border regions) is comparatively low [69]. Differences to the German and French border regions were sizable: One-way ANOVAs with subsequent Scheffé tests were significant at p < 0.01.…”
Section: Resultssupporting
confidence: 87%
“…Authors have indicated a comparatively weak civil society in Southern Europe (e.g. see Torcal and Montero, 2000;Van Oorschot et al 2006;Pichler and Wallace, 2007). This problem is even more strongly asserted for the formal civil society in Greece (Lyberaki and Paraskevopoulos, 2002;Mouzelis, 1995;Mouzelis and Pagoulatos, 2003) even though such poor presence is not uniformly weak (Sotiropoulos, 2004).…”
Section: Discussion -Managerial Relevancementioning
confidence: 99%
“…offered with a seven category response scale ranging from 'never' (0) to 'every day' (6). This survey question has been used in several studies on social networks (Pichler and Wallace 2007;Reeskens and van Oorschot 2014). 6 The second moderator variable is religious practice, which was surveyed by the question ''Apart from special occasions such as weddings and funerals, how often do you attend religious services nowadays?''…”
Section: Moderator Variablesmentioning
confidence: 99%